Pengaruh Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa Sekolah Dasar - Azura, Wan; Sari, Ira; Juniar, Intan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Parenting patterns have an important role in increasing student learning motivation, this affects student activities both at school and student habits for studying at home. This study aims to determine the effect of differences in parental parenting patterns on the learning motivation of fourth-grade students at Sam-Sam 017 Public Elementary School, as well as to determine the effect of each type of democratic, authoritarian, and permissive parenting patterns on student learning motivation. This study uses a quantitative approach with an ex post facto research design. The sample in this study was all 45 students in grades IV-A and IV-B, taken through a total sampling technique. The data instrument in this study was a questionnaire. Based on the research that has been done, it was found that parental parenting patterns significantly influence student learning motivation with a significance value of 0.002 <0.05, meaning that parental parenting patterns influence student learning motivation. The differences in parenting styles of each parent have different influences which are analyzed by the respective ANOVA tests, namely authoritarian (0.000<0.05), democratic (0.019<0.05), and permissive (0.082>0.05) so that authoritarian parenting styles in this digital technology era have a very significant influence compared to democratic parenting styles on learning motivation. However, permissive parenting styles do not affect the motivation of fourth grade students at Sam-sam 017 Public Elementary School. The implications of these findings indicate that the parenting styles applied by parents have different impacts on children's learning motivation, thus requiring parents' awareness to choose parenting approaches that optimally support learning motivation.